SPATIAL DIVERSITY OF SOCIO-ECONOMIC DEVELOPMENT OF THE POMERANIAN VOIVODESHIP (Research Bulletins of the Faculty of Economic Sciences, 2019)
The purpose of the article is to determine the level of socio-economic development of the poviats of the Pomeranian Voivodeship and to examine its change over the years 2006 and 2016. All poviats of the Pomeranian voivodship were analyzed, excluding cities with poviat status. The calculations were carried out using the synthetic measure method.For selected variables, synthetic measures have been determined for individual groups of development factors: economic, ecological, social, and political and institutional, as well as a general synthetic measure. This allowed for grouping poviats into classes with a similar level of socio-economic development, and for ordering them from the strongest to the least developed. The results of the analysis showed that the poviats of the Pomeranian Voivodeship are characterized by a large spatial diversity in terms of socio-economic development. Considering the years 2006 and 2016, poviats with a higher level of socio-economic development were located around the Tri-City area, while the least developed were the peripheral poviats of the voivodship.
Keywords: socio-economic development, synthetic measure, Pomeranian voivodeship